2009
DOI: 10.1016/s0968-8080(09)34478-x
|View full text |Cite
|
Sign up to set email alerts
|

Decriminalising homosexuality in India

Abstract: This paper examines the successful fight against the provision in Section 377 of the Penal Code of India that criminalised private consensual sex between adults of the same sex. This law had led to serious discrimination against people engaging in homosexual acts, who were subjected to frequent beatings and blackmail attempts by police, who used the threat of prosecution against them. NGOs working with sexual minorities have also been harassed and sometimes charged under Section 377. By stigmatising homosexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(36 citation statements)
references
References 3 publications
1
35
0
Order By: Relevance
“…Male-to-male sex is still be heavily stigmatised in India, despite the recent 'reading-down' of 'anti-sodomy laws' (section 377 of the Indian penal code) and albeit given significant social and cultural complexity regarding ways in which people of same-sex sexual orientation might often be socially ignored or culturally marginalised as much as being explicitly prejudiced against (Boyce and khanna 2011;Misra 2009). Given this, issues pertaining to reluctant condom use among men who have sex with men remain especially pertinent and complex.…”
Section: Resultsmentioning
confidence: 99%
“…Male-to-male sex is still be heavily stigmatised in India, despite the recent 'reading-down' of 'anti-sodomy laws' (section 377 of the Indian penal code) and albeit given significant social and cultural complexity regarding ways in which people of same-sex sexual orientation might often be socially ignored or culturally marginalised as much as being explicitly prejudiced against (Boyce and khanna 2011;Misra 2009). Given this, issues pertaining to reluctant condom use among men who have sex with men remain especially pertinent and complex.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the challenges, laws have been changed to allow clean syringes and needles to be distributed and exchanged by injection drug users (Mathers et al, 2010); sexual relations between men have been de-criminalized in countries such as Nepal and India, facilitating better access to health services (Misra, 2009, UNDP, 2011; and microfinance initiatives in Africa (Pronyk et al, 2006) and work with marginalized young men in Brazil (Barker, 2001) have shown that negative gender attitudes can be modified (Pulerwitz & Barker, 2008), laying the foundations for a more encompassing response (UNAIDS, 2010). In all of these efforts, education has had a key role to play even though the term education itself may not be used in the published write-ups-by providing knowledge and understanding, by spreading news of innovation and success, and by facilitating the development of a more supportive environment for HIV prevention and care.…”
Section: Prevention Educationmentioning
confidence: 99%
“…At the time of data collection, consensual adult same-sex sexual relationships were criminalized under section 377 of the Indian Penal Code (Misra, 2009). …”
Section: Methodsmentioning
confidence: 99%